Discalculia: como utilizar a ludicidade a favor do professor e do aluno - Rodrigues, Michele Aparecida Cerqueira (2021)
The human being, from a very early age, develops his first mathematical notions that can be better observed by teachers in the classroom. Mathematics is composed of four axes: treatment of information, numbers and operations, magnitudes and measures, space and form. According to the RCN's (Referencial Curricular Nacional), which comprise Early Childhood Education (BRASIL, 1998) and the 1st of Elementary School, only the last three are worked on. The first, information processing, is inserted only from the 2nd year of Elementary School, according to the PCN's. During Early Childhood Education, it is possible to find out if the student has any abnormality present in the continuous assessments made by the teachers in one or more of these axes, in order to previously detect any learning disorder. Obviously, the in-depth study of each case must be done by a psychopedagogue. Dyscalculia is one of these disorders that represents between 3% to 6% of children who are of school age. Therefore, teachers and guardians must pay attention to the signals emitted by children.